Absolute agreement and consistency of the OptoGait system and Freemed platform for measuring walking gait. (December 2022) - Núñez-Trull, Alejandro; Alvarez-Medina, Javier; Jaén-Carrillo, Diego; Roche-Seruendo, Luis E.; Gómez-Trullén, Eva
Highlights: Optogait system and Freemed platform are valid portable systems for gait analysis. Optogait exhibits higher accuracy for functional foot rockers identification. The interchangeable use of these portable systems should be avoided. Functional foot rockers analysis may aid in assessing and monitoring walking gait. Abstract: The gait cycle can be divided into four functional rocker units. Although the widespread use of the OptoGait (OG) system and the Freemed (FM) platform, their accuracy has not been tested. An observational study was completed with eighteen healthy volunteers to determine the accuracy of OG and FM for overground walking gait analysis. The pairwise comparison between data obtained from OG, FM and high-speed video analysis revealed significant differences for most of the measurements ( p  < 0.05). ICCs revealed an excellent absolute agreement between measurements (ICCs > 0.94) for all measures for OG systems compared to video-analysis. When considering FM vs. video-analysis, ICCs showed good absolute agreement for rocker 1 (ICC = 0.86) and 3 (ICC = 0.82), excellent for rocker 2 (ICC = 0.93) and poor (ICC < 0.5) for rocker 4. Bland-Altman plots (95% limits of agreement) revealed heteroscedasticity of error for OG in all variables for foot rockers (r 2  > 0.1) while no heteroscedasticity of error was found when using FM (r 2  < 0.1). This study indicates that the OG system and the FM platform can provide consistent foot rockers values when walking at a constant velocity. The differences between the systems assessed and their agreement and consistency values advise against their interchangeable use.